The Miracles Language of The Holy Quran" A Comparative Study" - Al-Barwary, Zerevan Q.A.; Oula, Amir R. (Humanities Journal of University of Zakho, 2017)
This article endeavors to study the miracles language of the holy Quran, which appears in a clear Arabic Language in line with what was familiar with the most explicit Arab and nation’s tongue. It surprised through its rhetoric and unique style also paid much attention from the world through its communication, clarity as well as graphic of miraculous. Additionally, this miracle that is the authentic of all other kinds of miracles, it moreover looks for the spotless issue, which Allah bestowed with Arabs to speak like the Holy Quran. First foremost, this study attempts to clear up Ibrahim bin Sayar’s system and its inception, which is affected through the standpoint of Brahmin. Thus, the outcome of this study leads to generate the conclusion of this article to be contained the lack of pure evidence, corruption statement as well as invalidity.